Investigating the mechanical properties of GeSn nanowires. Issue 28 (10th July 2019) - Kosmaca, Jelena; Meija, Raimonds; Antsov, Mikk; Kunakova, Gunta; Sondors, Raitis; Iatsunskyi, Igor; Coy, Emerson; Doherty, Jessica; Biswas, Subhajit; Holmes, Justin D.; Erts, Donats
Abstract : Mechanical resonance and bending tests on crystalline GeSn nanowires revealed size-dependent Young's moduli and bending strengths close to theoretical values. Abstract : Germanium tin (GeSn) has been proposed as a promising material for electronic and optical applications due to the formation of a direct band-gap at a Sn content >7 at%. Furthermore, the ability to manipulate the properties of GeSn at the nanoscale will further permit the realisation of advanced mechanical devices. Here we report for the first time the mechanical properties of GeSn nanowires (7.1–9.7 at% Sn) and assess their suitability as nanoelectromechanical (NEM) switches. Electron microscopy analysis showed the nanowires to be single crystalline, with surfaces covered by a thin native amorphous oxide layer. Mechanical resonance and bending tests at different boundary conditions were used to obtain size-dependent Young's moduli and to relate the mechanical characteristics of the alloy nanowires to geometry and Sn incorporation. The mechanical properties of the GeSn nanowires make them highly promising for applications in next generation NEM devices.